2013
DOI: 10.1111/ele.12154
|View full text |Cite
|
Sign up to set email alerts
|

How species richness and total abundance constrain the distribution of abundance

Abstract: The species abundance distribution (SAD) is one of the most intensively studied distributions in ecology and its hollow-curve shape is one of ecology's most general patterns. We examine the SAD in the context of all possible forms having the same richness (S) and total abundance (N), i.e. the feasible set. We find that feasible sets are dominated by similarly shaped hollow curves, most of which are highly correlated with empirical SADs (most R(2) values > 75%), revealing a strong influence of N and S on the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
164
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(168 citation statements)
references
References 47 publications
3
164
1
Order By: Relevance
“…It is already well established that models based on different processes can yield equivalent models of the SAD, i.e., they predict distributions of exactly the same form (Cohen, 1968; Boswell & Patil, 1971; Pielou, 1975; McGill et al, 2007). To the extent that SADs are determined by random statistical processes, one might expect the observed distributions to be compatible with a wide variety of different process-based and process-free models (Frank, 2009; Frank, 2011; Locey & White, 2013). Regardless of the underlying reason that the models performed similarly, our results indicate that the SAD usually does not contain sufficient information to distinguish among the possible statistical processes—let alone biological processes—with any degree of certainty (Volkov et al, 2005), though it is possible that this result differs in marine systems (see Connolly et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It is already well established that models based on different processes can yield equivalent models of the SAD, i.e., they predict distributions of exactly the same form (Cohen, 1968; Boswell & Patil, 1971; Pielou, 1975; McGill et al, 2007). To the extent that SADs are determined by random statistical processes, one might expect the observed distributions to be compatible with a wide variety of different process-based and process-free models (Frank, 2009; Frank, 2011; Locey & White, 2013). Regardless of the underlying reason that the models performed similarly, our results indicate that the SAD usually does not contain sufficient information to distinguish among the possible statistical processes—let alone biological processes—with any degree of certainty (Volkov et al, 2005), though it is possible that this result differs in marine systems (see Connolly et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…The SAD is one of the most widely studied patterns in ecology, leading to a proliferation of models that attempt to characterize the shape of the distribution and identify potential mechanisms for the pattern (see McGill et al, 2007 for a recent review of SADs). These models range from arbitrary distributions that are chosen based on providing a good fit to the data (Fisher, Corbet & Williams, 1943), to distributions chosen based on the most likely states of generic random systems (Frank, 2011; Harte, 2011; Locey & White, 2013), to models based more directly on ecological processes (Tokeshi, 1993; Hubbell, 2001; Volkov et al, 2003; Alroy, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this relationship applies to samples from different systems and does not pertain to cumulative patterns (e.g., collector's curves), which are based on resampling (20)(21)(22). Recent studies have also shown that N constrains universal patterns of commonness and rarity by imposing a numerical constraint on how abundance varies among species, across space, and through time (23,24). Most notably, greater N leads to increasingly uneven distributions and greater rarity.…”
mentioning
confidence: 99%
“…In addition to considering sampling (unveiling) effects, one may ask whether the observed SAD for a particular year can simply result from simultaneous statistical constraints of total species richness and total abundance (i.e., statistical artifact) without invoking any ecology (Locey and White 2013). To address this issue, we performed two additional null model analyses (Appendix C).…”
Section: Time Series and Functional Data Analysesmentioning
confidence: 99%